Coherent optical spectroscopy characterization of the magnetic properties of oriented Fe3O4 nanoparticles. Issue 1 (1st March 2022) - Taskova, E; Alipieva, E; Kolev, S; Koutzarova, T; Brazhnikov, D
Abstract: Magnetite (Fe3 O4 ) nanoparticles are widely used in microwave components, such as microwave absorbers and anti-reflection coatings. Their magnetic properties are important for these applications. In this work, the weak magnetic field created by the Fe3 O4 nanoparticles was estimated using a coherent-spectroscopy all-optical method for measurement of weak magnetic fields. Both the magnitude and the direction of the magnetic field were evaluated through the position and amplitude of a magneto-optical resonance obtained in a paraffin-coated sensor cell containing Rb vapors. A pump-probe scheme was used to prepare a high-contrast magneto-optical resonance. Different possible geometries related to this concept are discussed, including sensor miniaturization.